Financial Wellbeing of Poor Households in Eastern Indonesia: Role of Digital Financial Inclusion - Maria Oktaviani Lede; Yohanes Rafael Benu; Daniel Putra Nggili (Journal of Economics Business Industry, 2026)
This study examines the determinants of financial wellbeing among poor households in Eastern Indonesia, with particular emphasis on the mediating role of digital financial inclusion. Focusing on East Nusa Tenggara (NTT) and West Nusa Tenggara (NTB), the study addresses the persistent financial vulnerability of poor households living in regions characterized by high poverty, limited formal financial access, and uneven digital infrastructure. Primary survey data were collected from 405 poor households whose income fell below the provincial poverty line, consisting of 248 respondents from NTT and 157 respondents from NTB. The data were analyzed using partial least squares structural equation modeling (PLS-SEM), followed by multigroup analysis to compare provincial differences. The findings show that financial behavior, financial literacy, and digital financial inclusion have significant positive effects on household financial wellbeing. However, digital literacy, digital financial service infrastructure, and financial service providers do not directly affect financial wellbeing. Instead, digital financial inclusion fully mediates the effects of infrastructure and financial service providers on financial wellbeing. The multigroup analysis reveals that digital financial inclusion has a stronger impact on financial wellbeing in NTT, while infrastructure and financial service providers have stronger effects on digital financial inclusion in NTB. These results highlight the importance of strengthening digital financial inclusion as a strategic pathway to improve the financial wellbeing of poor households. Policy interventions should prioritize financial education, affordable digital financial products, reliable digital infrastructure, and locally adapted financial services for underserved communities in Eastern Indonesia.